Artistas ambulantes. Un reto desde el encierro (2021)
In this paper, "Itinerant Artists, a challenge from the running of the bulls", we will tell and reflect on the creative process in the joint editing courses of the Antonio Nariño University Degree in Performing Arts, and how the language of radio theatre emerges in the virtual training of future graduates, resulting in the radio dramatised "Itinerant Artists".